The Economic Potential of the Partnership Pattern Between Laying Chicken Pullet Breeders with PT. Saredo Jaya Abadi - Daroini, Ahsin (Prosiding Seminar, 2022)
The partnership pattern is a chicken farming business carried out with the plasma core pattern, namely a partnership between partner breeders and partner companies, where the partner group acts as the plasma, while the partner company is the core. This study aims to determine the economic potential of the partnership pattern between laying hens and pt. saredo jaya eternal. Determination of the number using simple random sampling method with a sample of 2 farmers and 1 director of PT. Saredo Jaya Abadi. The data analysis used is descriptive qualitative analysis and case study approach. The results of the study that the economic potential of the partnership pattern between laying hens and PT. Saredo Jaya Abadi has the advantage that farmers get, in 1 laying pullet chicken, farmers get a profit of Rp. 3,860.00.